Dose Optimization for Computed Tomography Localizer Radiographs for Low-Dose Lung Computed Tomography Examinations - Schmidt, Bernhard Magnus Wilhelm; Hupfer, Martin; Saltybaeva, Natalia; Kolditz, Daniel; Kalender, Willi Alfred (Investigative Radiology, 2017)
INTRODUCTION: Recent studies have shown a substantial reduction of radiation dose from computed tomography (CT) scans down to 0.1 mSv for lung cancer screening and cardiac examinations, when applying optimization techniques. Hence, CT localizer radiographs (LRs) might now be considered a significant contributor to the total dose of the CT examination. We investigated in our study the potential for reducing dose of the LRs by adapting the patient-specific acquisition parameters of the LR. MATERIALS AND METHODS: Localizer radiographs covering the lungs were acquired on 2 clinical scanners (64 slices, conventional detector [CD]; 96 slices, fully integrated detector [ID]) for 3 semianthropomorphic phantoms, representing a slim, a normal, and an obese adult. Starting at 120-kV tube voltage and 250-mA current were reduced until the image quality of the LR, and thereby the accuracy of the automatic exposure control was compromised; this was defined as a deviation of measured attenuation values in the center of the LR of more than 5% from the reference values measured at the highest tube voltage and current. Subsequent Monte Carlo calculations on anthropomorphic phantoms were performed to calculate organ and effective dose values for the respective optimal settings. In addition, effective dose values normalized to CTDIvol for tube voltages ranging from 60 to 160 kV were determined for the different combinations of phantom sizes, sexes, and LR views to evaluate dose efficiency. RESULTS: For the CD scanner, the optimal LR settings depended strongly on phantom size. Higher tube voltage and current were necessary for the larger phantoms. The ID scanner showed uncompromised LR quality for all phantoms using the lowest possible tube voltage-tube current combination of 80 kV and 20 mA. Depending on patient size and LR direction, effective dose values for the optimal settings ranged from 6 to 53 μSv and 3 to 11 μSv for the CD and ID scanner, respectively. For the example of an anterior-posterior LR on a normal patient, using the optimal settings instead of the standard settings on the ID scanner reduced LR dose from 53 μSv (120 kV, 30 mA) to 10 μSv (80 kV, 20 mA). The simulations for the different tube voltages show that effective dose and CTDIvol behave similarly for different views and patient sizes. However, the tube voltage level itself impacts the relationship between CTDIvol and effective dose, by up to a factor of 2. DISCUSSION: Dose from LRs may contribute significantly to the total effective dose of low-dose CT examinations such as lung cancer screening. Optimal LR settings can reduce LR dose substantially, but adaptations have to consider scanner characteristics, detector technology, and patient size. Thus, for low-dose CT examinations, such as cardiac examinations and lung cancer screening, LR optimization may result in a significant dose reduction and thereby in a substantial reduction of total dose.
EVALuna2:33261